(untitled) (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
. In this era of globalization, many issues are becoming increasingly widespread and heated, one of which is the LGBT issue, which seems to be growing in popularity day by day, apparently without a solution. In Indonesia, where the majority of the population is Muslim and Eastern cultures clearly reject LGBT behavior, which is often considered taboo. However, many Indonesian teenagers are now beginning to open up about LGBT issues. LGBT is a deviant behavior that currently has both pro and contra groups towards LGBT people. This study aims to determine the perceptions of students at Sultan Syarif Kasim Riau State Islamic University regarding LGBT, using Albert Bandura’s social cognitive theory as a basis for clarifying this research. This study was conducted using a quantitative method, data were collected through the distribution of a questionnaire containing 25 items to 30 students at Sultan Syarif Kasim Riau State Islamic University as respondents. In this study, a validity test was conducted using a significance level of 0.361 and the results were 18 valid items and 7 invalid items. This study also conducted a reliability test using the Cronbach’s Alpha formula and used a benchmark value of 0.7 and the results were declared reliable with a Cronbach’s Alpha of 0.726 which is greater than 0.7. In this study, it was also found that students have a positive perception of LGBT perpetrators, although respondents also disagree and do not support LGBT behavior, but they will accept LGBT perpetrators to be guided and directed so they can return to their normality